A review of empirical data of sustainability initiatives in university campus operations - Amaral, Ana Rita (2020)
Given the need to actively address the challenges of climate change, university leaders have a growing interest in reducing their campuses’ environmental impact. This article carries out a comprehensive literature review on the implemented actions and initiatives in university campuses reported in scientific publications. In addition, case studies carried out in universities are also reviewed, giving particular attention to the methods and tools used, targeting the current trends in sustainable campus scientific research. Key actions and initiatives were identified and categorized according to Energy, Buildings, Water, Waste, Transportation, Grounds, Air and Climate, and Food. Results show that the increase in energy generation on campus and the decrease of energy consumption in buildings are by far the leading policies adopted, however with limited dissemination of their impact. Moreover, there seems to be a tendency for countries with higher income economies to engage in initiatives that involve greater investment, such as the adoption of renewable energy systems or efficient buildings systems. The need to establish an integrated framework to disseminate and monitor the impact of key actions and their feasibility is suggested, in order to leverage strategic programs and actions, helping to optimize investments, and leading advances towards a sustainable university campus.